Pengaruh Tax Avoidance, Earnings Management, Profitabilitas Terhadap Cost Of Debt Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di BEI Tahun 2021-2023 - Ni Made Sri Indah Lestari; Putu Sri Arta Jaya Kusuma (Jurnal Akuntansi dan Pajak, 2025)
This study aims to examine the effect of tax avoidance, earnings management, and profitability on the cost of debt. The population used in this study are mining sector companies that have been listed on the Indonesia Stock Exchange (IDX) for 2021-2023. The research sample was taken using purposive sampling method which obtained 45 mining sector companies or 135 annual financial reports. The data used is secondary data in the form of the company's annual financial statements obtained from the Indonesia Stock Exchange (IDX). The data analysis techniques in this study are descriptive statistics, classical assumption tests and multiple linear regression tests. The software used is SPSS 25. The test results of this study use multiple linear regression analysis. The results showed that tax avoidance has no effect on the cost of debt. Earnings management has no effect on the cost of debt. Profitability has a positive effect on the cost of debt.